2012
DOI: 10.1186/1471-2458-12-466
|View full text |Cite
|
Sign up to set email alerts
|

The association between neighborhood greenness and cardiovascular disease: an observational study

Abstract: BackgroundPrevious studies have demonstrated links between cardiovascular disease and physical inactivity and poor air quality, which are both associated with neighborhood greenness. However, no studies have directly investigated neighborhood greenness in relation to coronary heart disease risk. We investigated the effect of neighborhood greenness on both self-reported and hospital admissions of coronary heart disease or stroke, accounting for ambient air quality, socio-demographic, behavioral and biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(118 citation statements)
references
References 13 publications
5
112
0
1
Order By: Relevance
“…These outcomes are hard to combine with mortality estimates if little information on the population structure is available. An Australian study showed that the odds of hospitalization for heart disease or stroke were 37% lower among adults exposed to the highest tertiles of greenness compared to those exposed to the lowest tertiles (Pereira et al 2012). A study conducted in the USA evaluating the influence on mortality of the loss of 100 million trees due to the emerald ash borer, an invasive forest pest, observed that in the infested areas mortality due to CVD and low respiratory tract illnesses was increased (Donovan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are hard to combine with mortality estimates if little information on the population structure is available. An Australian study showed that the odds of hospitalization for heart disease or stroke were 37% lower among adults exposed to the highest tertiles of greenness compared to those exposed to the lowest tertiles (Pereira et al 2012). A study conducted in the USA evaluating the influence on mortality of the loss of 100 million trees due to the emerald ash borer, an invasive forest pest, observed that in the infested areas mortality due to CVD and low respiratory tract illnesses was increased (Donovan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An observational study in Australia demonstrated that a greater variability in landscape combining trees and open green space was associated with reduced risk of cardiovascular disease and stroke (Pereira et al 2012). The authors hypothesized that variability in neighbourhood greenness reflects two factors promoting physical activity -an aesthetically pleasing natural environment and access to urban destinations.…”
Section: Reduced Cardiovascular Morbidity and Mortalitymentioning
confidence: 99%
“…An urban sprawl index is a composite measure commonly identified by four characteristics: low residential density; rigidly separated homes, shops, and workplaces; roads with large blocks and poor access; and a lack of well-defined activity centers (45). Public spaces such as green or open spaces are linked to various health outcomes in research, including violence (62), general health and well-being (55, 109), obesity (86), and cardiovascular health (77). Although traditional metrics of access to parks using proximity indicators can be used, one can apply a variety of indices to capture multiple dimensions.…”
Section: Built Environmentmentioning
confidence: 99%